Effect of within family selection on litter weight and body weight in rabbits - NARAYAN, A D; RAWAT, S; SAXENA, M C (The Indian Journal of Animal Sciences, 2013)
From the selection for’high litter weight at 6 weeks in one line and high body weight at 16 weeks in the other line it was observed that selection for high litter weight at 6 weeks caused reduction in average litter weight. The 16 weeks body weight responded to selection in upward dirertion and caused correlated increase of litter weight at 6 weeks. The genetic correlation obtained from this double selection experiment was 0.41 between litter weight at 6 weeks and body weight at 16 weeks. The control line did not show any trend. The control reduced the variability of response in litter weight at 6 weeks but did not reduce the ariability of response in weight at 6 weeks and height at 16 weeks.